ANALYSIS OF PRE-SERVICE TEACHERS' COGNITIVE PROFILES - Zacharová, Zlatica Jursová; Lemešová, Miroslava; Sokolová, Lenka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In recent years there has been increased attention to the problem of teachers' competences. The need for developing critical thinking in schools turns the focus also on the teachers' cognitive skills including not only intelligence but also cognitive reflection and implicit theories of intelligence. This study aimed to analyse pre-service teachers' (N = 344) cognitive profiles covering data from cognitive reflection test (CRT), implicit theories of intelligence test and Mannheim intelligence test (MIT, measuring verbal, numerical and spatial abilities). Significant correlations were found between cognitive reflection and other cognitive abilities. However, the implicit theories of intelligence seemed to be independent of cognitive abilities. Significant differences between senior and junior pre-service teachers were found in cognitive reflection and two MIT items. Based on the presented results, we discuss the assessment of pre-service teachers’ competences and the development of critical and higher order thinking in pre-gradual teacher education.